Определение параметров электромагнитных видеоимпульсов для увеличения иммуноглобулинов в молозиве коров - Торчук, М. В. (НТУ "ХПИ", 2014)
На сохранение новорожденных телят в первые дни жизни особенно влияет количество иммуноглобулина в молозиве и молоке коров. Иммуноглобулины выполняют ведущую роль в гуморальном иммунитете, их уровень отражает функциональную активность В–лимфоцитов. Поэтому для увеличения иммуноглобулинов в молозиве и молоке новотельных коров были проведены исследования по определению биотропных параметров импульсного электрического поля для воздействия на молочную железу новотельных коров с целью увеличения иммуноглобулинов класса LgG и LgM в молозиве и молоке

Due to inadequate feeding of pregnant cows and a violation of their upkeep technology immunodeficiency is being observed among birth calves. Thus calves require preventive correction of immune status. The preservation of newborn calves in the first days of life is being affected by the amount of immunoglobulins in colostrum and milk cows. Immunoglobulins perform a leading role in humoral immunity, their level reflects the functional activity of B-lymphocytes. Therefore, to increase immunoglobulins in colostrum and milk of cows studies were made to determine the parameters biotropic pulsed electric field (pulse amplitude, frequency and pulse repetition period; exposure level) which effects the mammary gland of cows and allows to increase immunoglobulin LgG LgM and colostrum and milk. Immunoglobulins in colostrum and milk of cows that enter the body of newborn calves prevent the appearance of immunodeficiency and deterrent effect of neonatal pathology in calves
Determination of parameters of electromagnetic pulses which allow to increase immunoglobulins in colostrum of cows
Keywords: молочная железа коров; импульсы электрического поля; молоко; телята; bovine mammary; pulses of electric field; colostrum of cows; immunoglobulins